Entre Brasil e Europa: a revolução cultural do século XIX (Almanack, 2019)
Resenha do livro: ABREU, Márcia; SILVA, Ana Cláudia Suriani. The Cultural Revolution of the Nineteenth Century: Theatre, the Book-Trade and Reading in the Transatlantic World. I. B. Tauris: London, New York, 2016. 309 p.